2012
DOI: 10.1007/s00383-012-3078-6
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic hernioraphy: a better approach for recurrent hernia in boys?

Abstract: We propose that laparoscopic repair in recurrent childhood inguinal hernia cases, developed after open repair, avoids entering a fibrotic inguinal canal, making the procedure easier and shorter. Laparoscopic herniorrhaphy is a good alternative option in recurrent childhood hernia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…Thus, several surgeons prefer a “8” shape suturing after pouch suturing in order to strengthen the transversalis fascia. [2] In our experience of huge hernia, the transversalis fascia was observed after suturing the internal ring. If the fascia is still loose, an “8” shape suture was performed as an additional procedure, which was rather feasible in the TLHK procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, several surgeons prefer a “8” shape suturing after pouch suturing in order to strengthen the transversalis fascia. [2] In our experience of huge hernia, the transversalis fascia was observed after suturing the internal ring. If the fascia is still loose, an “8” shape suture was performed as an additional procedure, which was rather feasible in the TLHK procedure.…”
Section: Discussionmentioning
confidence: 99%
“…[1] With the development in technology, several medical centers adopted laparoscopic hernia repair in children as the best option for herniorrhaphy, replacing the open procedure due to minimal invasiveness and better cosmetic effect. [27] Three types of laparoscopic approaches are available for hernia repair, 3 ports (conventional laparoscopic hernia repair, CL), 2 ports (TP), and single incision (SIL). CL commonly requires 3 working ports ranging from 3 to 5 mm, and each increasing port might be associated with increasing morbidity and pain.…”
Section: Introductionmentioning
confidence: 99%
“…Conversion to open in single patient was required due to adherent omentum which could not be reduced laparoscopically and operating time was also more than 40 minutes in this patient only. Various authors have reported different conversion rates and it varies from 0 to 10% [21,22]. Laparoscopic repair in recurrent childhood inguinal hernia cases, developed after open repair, avoids entering a fibrotic inguinal canal, making the procedure easier and shorter and hence laparoscopic hernia repair is a good alternative options in recurrent childhood hernia [23].…”
Section: Discussionmentioning
confidence: 99%
“…Daha önce başarısız açık cerrahi geçirerek nüks eden inguinal hernilerde, ikincil açık cerrahi girişim, bozulmuş anatomik yapı ve fibrotik değişiklikler nedeniyle, vaz deferens veya testiküler damarların yaralanması açısından artmış riskler taşır. Bu hastalardaki laparoskopik görünüm, cerrahi müdahale yapılmamış hastalardan farksız olduğundan, laparoskopik onarım ek riskler taşımaz (13) .…”
Section: Discussionunclassified